1998
DOI: 10.1074/jbc.273.34.21569
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 15-Lipoxygenase by Human Colorectal Carcinoma Caco-2 Cells during Apoptosis and Cell Differentiation

Abstract: We studied arachidonic acid metabolism and the expression of cyclooxygenase (Cox) and 15-lipoxygenase (15-LO) in the human colorectal carcinoma cell line, Caco-2, which undergo apoptosis and cell differentiation in the presence of sodium butyrate (NaBT). Caco-2 cells expressed very low levels of Cox-1 but highly expressed Cox-2. NaBT treatment shifted the arachidonic acid metabolites by cell lysates from prostaglandins to 15-hydroxyeicosatetraenoic acid, indicating the presence of a 15-LO. Linoleic acid, an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 44 publications
5
82
0
Order By: Relevance
“…In human colorectal carcinoma Caco-2 cells, sodium butyrate induces the expression of reticulocyte 15-LO-1, and these cells undergo differentiation and apoptosis (5). This study provided the first evidence that 15-LO-1 is clearly expressed in human colorectal carcinoma cells, and it was subsequently shown that the 15-LO-1 is uniquely regulated by histone acetylation (6).…”
Section: Lipoxygenases (Los)mentioning
confidence: 64%
“…In human colorectal carcinoma Caco-2 cells, sodium butyrate induces the expression of reticulocyte 15-LO-1, and these cells undergo differentiation and apoptosis (5). This study provided the first evidence that 15-LO-1 is clearly expressed in human colorectal carcinoma cells, and it was subsequently shown that the 15-LO-1 is uniquely regulated by histone acetylation (6).…”
Section: Lipoxygenases (Los)mentioning
confidence: 64%
“…We used Caco-2 cells as a model system to study the mechanisms that regulates COX-2 expression in colon cancer cells. Caco-2 cells express COX-2, but not COX-1, mRNA levels, expression being variable in di erent studies probably due to di erent clones of Caco-2 cells used and/or di erent experimental conditions (Kutchera et al, 1996;Tsujii et al, 1997Tsujii et al, , 1998Kamitani et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…11 Therefore, it is not surprising that activation of lipoxygenases has been associated to programmed death of different cells and tissues, induced by different, unrelated stimuli (Table 1 and references therein). Several studies have shown the proapoptotic activity of 5-LOX, 15,23 of leukocyte type 12-LOX, 21,26 and of 15-LOX, 24,28 and have indicated molecular targets for lipoxygenase interaction able to contribute to the induction of apoptosis (Table 2 and references therein). However, also anti-apoptotic effects of LOXs have been reported, mainly based on the observation that LOX inhibitors, most often nordihydroguaiaretic acid (NDGA) and MK886, had pro-apoptotic activity.…”
Section: Lipoxygenase Involvement In Apoptotic Pathwaysmentioning
confidence: 99%